Exploring Outward FDI and the Choice of Destination: Evidence from Swedish Firm-Level Data - Zouheir El-Sahli; Joakim Gullstrand; Karin Olofsdotter (Lund University, School of Economics and Management, Department of Economics, 2016)
Using Swedish firm-level data on all firms and their affiliates abroad, we investigate what observable firm and country characteristics affect the size of affiliate firms in a particular destination. We employ the richness of the data to investigate the importance of destination country factors in explaining firm outward FDI activities and distinguish between the factors that affect such activities in manufacturing versus services firms as well as vertical versus horizontal investments. Our results lend support to existing theories of multinational activity, including observable differences between vertical and horizontal manufacturing firms, as well as between services and manufacturing FDI firms.
Keywords: F10; F20; 330; outward FDI; globalization; FDI destination; heterogeneous firms